-7e+9=-17-5e

Simple and best practice solution for -7e+9=-17-5e equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7e+9=-17-5e equation:



-7e+9=-17-5e
We move all terms to the left:
-7e+9-(-17-5e)=0
We add all the numbers together, and all the variables
-7e-(-5e-17)+9=0
We get rid of parentheses
-7e+5e+17+9=0
We add all the numbers together, and all the variables
-2e+26=0
We move all terms containing e to the left, all other terms to the right
-2e=-26
e=-26/-2
e=+13

See similar equations:

| -8x-10-x=-12x+20 | | 0.5y-1.25=3.5 | | 400=-10x | | -4x71=43 | | 70+x+32=90 | | 8+5v=38 | | 26=y+19 | | -4.2(x)=2.1 | | 1.4*12=y | | 2/4f+20=120 | | 5x-18=15x-12=180 | | 4x-1=3x+3=180 | | 2=3l/4 | | y=7.5+40 | | 25x10=300 | | 8=u/2-12 | | 3(6x+2)=2(9x-1) | | 6000+75*(x/90)=x | | x^2-2=83 | | 0.45x+3=0.3x+2 | | x^2/(2)=83 | | 3x=17/12 | | 20+2(3x+10)=2x | | x^2/2=83 | | 10r=1.000 | | 5.8/3x+6=3.8x+4.32 | | 2(4x+1)-5x=8 | | 3(x+2)(-2)=0 | | 4.4x-3.2+2x=6.4 | | 2x-5)(7x+2)=0 | | 5x+22+2x+26=180 | | 10y-1=99 |

Equations solver categories